2003
DOI: 10.1172/jci200316950
|View full text |Cite
|
Sign up to set email alerts
|

Graft-versus-host disease can be separated from graft-versus-lymphoma effects by control of lymphocyte trafficking with FTY720

Abstract: Graft-versus-host disease (GvHD) mediated by donor T cells recognizing host alloantigens is associated with beneficial graft-versus-tumor effects in recipients of allogeneic hematopoietic cell transplants. Since leukemias and lymphomas reside largely within the lymphohematopoietic system, we have proposed that the desired graft-versus-leukemia or graft-versus-lymphoma effect can be separated from the complication of GvHD by confinement of the graft-versus-host alloresponse to the lymphohematopoietic tissues. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(59 citation statements)
references
References 60 publications
0
59
0
Order By: Relevance
“…We did not observe any effect of CYM on the infiltration of donor T cells to the aGVHD organs at an early stage of the disease. Although it has been suggested that FTY720 may modulate lymphocyte trafficking, especially donor-derived T-cell infiltration into target organs, to inhibit aGVHD, 20,39,40 another recent study demonstrated that FTY720 did not inhibit donor effector T-cell trafficking into the aGVHD target organs. 41 The same report also showed FTY720 reduced the number of DCs in the target organs, which has been suggested to be the mechanism underlying aGVHD inhibition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not observe any effect of CYM on the infiltration of donor T cells to the aGVHD organs at an early stage of the disease. Although it has been suggested that FTY720 may modulate lymphocyte trafficking, especially donor-derived T-cell infiltration into target organs, to inhibit aGVHD, 20,39,40 another recent study demonstrated that FTY720 did not inhibit donor effector T-cell trafficking into the aGVHD target organs. 41 The same report also showed FTY720 reduced the number of DCs in the target organs, which has been suggested to be the mechanism underlying aGVHD inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,13 FTY720 has been shown to be a promising immunosuppressive agent for the treatment of autoimmune disease, promotion of solid organ engraftment and inhibition of aGVHD. 8,[14][15][16][17][18][19][20][21] However, the mechanism underlying the action of FTY720 is not completely known. Clinically, FTY720 mediates both lymphopenia and transient dose-dependent bradycardia on initial dosing in humans.…”
Section: Introductionmentioning
confidence: 99%
“…32 On the basis of the published clinical GVHD scores, each parameter was scored as follows: 0 ¼ normal, 1 ¼ mild, 2 ¼ moderate and 3 ¼ severe. 33 The maximal score was 12. For histological confirmation of GVHD, liver, colon and spleen were obtained from moribund animals or from necropsies.…”
Section: Assessment Of Gvhdmentioning
confidence: 97%
“…It has been shown to control some autoimmunities and allergic diseases as well as to suppress transplant rejection and graft vs. host disease (3). The drug has shown efficacy in advanced clinical trials for the treatment of multiple sclerosis (4).…”
Section: Introductionmentioning
confidence: 99%